PENILAIAN TINGKAT KESEHATAN BANK CENTRAL ASIA SYARIAH TAHUN 2010-2014 DENGAN MENGGUNAKAN PERHITUNGAN RASIO CAELS - PUTRI, NOVELYSTA (Jurnal Akuntansi AKUNESA, 2015)
Abstract The number of financial institutions both of conventional and sharia makes tight the challenges faced by the Asian Central Bank Sharia in trying to gain the trust of society as one of the new sharia bank in Indonesia. One way to achieve this is by measuring the health of bank using CAELS. Data processing was performed by descriptive analysis is to look for the calculation of the ratio of each variable, and then specify the results of the assessment are classified into composite rating of bank health. The results showed that the level of health BCA Sharia 2010-2014 period are included in the category of very healthy. The Bank also has the financial capability and strong risk control in the event of significant changes in the banking industry. Keywords : financial ratio, CAELS, health assessment, financial performance BCA Sharia